Milk Proteins - From Structure to Biological Properties and Health Aspects 2016
DOI: 10.5772/63433
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Interaction of Milk and Dairy Proteins with Aflatoxin M1

Abstract: In this chapter, up-to-date data regarding the nature of protein interaction with a contaminant such as aflatoxin M 1 (AFM 1) is detailed. Considering that AFM 1 is a relevant toxin present in milk and dairy products, it is important to understand such interaction. With this in mind, some specific features of protein chemistry and structure are discussed. AFM 1 presence and origin in milk and the latest approaches in AFM 1 chemical analysis with special attention to sample preparation techniques to eliminate m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 83 publications
(111 reference statements)
0
6
0
Order By: Relevance
“…Other dairy products (such as cheese, cream, ice-cream, etc.) were not included in this study due to the large technological diversity of these products in the two countries, as AFM1 has the capability to bind with various macromolecules, especially proteins [37]. This can lead to different distribution of AFM1 in products of the same type, depending on technology used.…”
Section: Methodsmentioning
confidence: 99%
“…Other dairy products (such as cheese, cream, ice-cream, etc.) were not included in this study due to the large technological diversity of these products in the two countries, as AFM1 has the capability to bind with various macromolecules, especially proteins [37]. This can lead to different distribution of AFM1 in products of the same type, depending on technology used.…”
Section: Methodsmentioning
confidence: 99%
“…This procedure may be coupled with a filtration step to remove the supplemented microbial agents. Noting that even without any microbial supplementation, the increase of contact between AFM1 and milk components including LAB and proteins such as casein may result in an increase in the binding of free AFM1, thereby decreasing AFM1 bioavailability in contaminated milk [148,149,150].…”
Section: Prospective Industrial Applicationsmentioning
confidence: 99%
“…There is evidence that nearly 30% of AFM 1 is associated with milk samples SNF, which is mainly due to the strong ability of the toxin to bind to milk samples proteins (Granados‐Chinchilla ). Therefore, higher AFM 1 levels in milk samples would be expected in milk samples collected in winter in the present study, since in this season higher percentages of milk samples TP and SNF were observed.…”
Section: Resultsmentioning
confidence: 99%